A Comparative Analysis of the Model of a Quality Assessment of Mathematics Subject: an Application of Differential Item Function and Differential Distractor Functioning - Sirikit, Ruangdech (Scholar: Human Sciences, 2014)
This study aimed to compare the efficiency of model of quality assessment of mathematics subject when applying 4 models of quality assessment. The data used in this study was secondary data from Trends in International Mathematics and Science Study (TIMSS) of 2007. Samples were composed of students, mathematic teachers who taught student samples and executives of 150 educational institutions where student samples were studying as well as 5,412 students. The study focused on mathematics subject with 14 papers of knowledge evaluation test on mathematics. There were 3 steps of data analysis – 1) investigate differential item functioning and differential distractor functioning with DDFS program 1.0; 2) analyze value added in the model of quality assessment using Value-Added Model with Hierarchical Linear Modeling (HLM) and 2 levels of analysis; and 3) investigate results of quality assessment of mathematics subject in the institutions with 4 different models which were 1) Undetected DIF-DDF & Adjusted; 2) Detect DIF & Adjusted; 3) Detect DIF-DDF & Unadjusted; and 4) Detect DIF-DDF & Adjusted. The results showed that the model of quality assessment of mathematics which had effect control in the level of students and educational institutions provided similar outcome of quality assessment of mathematics subject. The model 4 had the highest coefficient of determination (R2) at 52.04% followed by Model 1 and 2 which had the coefficient of determination (R2) at 51.96% and 51.86% respectively.